Characterization and optimization of Casimiroa (Casimiroa Edulis) fruit juice using Response Surface Methodology (RSM) - Tesfaye Zeru Genanew; Adamu Zegeye; Biniyam Tesfaye Banjaw (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Background: Casimiroa edulis fruit is an underutilized seasonal fruit of Ethiopia, and is a rich source of many medicinal and nutritional properties. Casimiroa edulis is a fruit with good sources of different nutrients (minerals, vitamins, phytochemicals, and energy). The fruit is found in different parts of the country, Ethiopia. However, there are no clear research shreds of evidence of the fruits on post-harvest handling, preservation, processing, and value addition.  Purpose of the study: The present study is aimed at the characterization and optimization of the enzyme-assisted casimiroa fruit juice clarification process based on selected quality parameters of the final product.  Methodology: D-optimal Mixture Design and RSM were used to investigate the level of ingredients and the effects of independent variables on physicochemical composition, functional properties, mineral values, and acceptability tests of casimiroa fruit juice. Graphical and numerical optimization was conducted to find the best variables conditions. Casimiroa fruit was treated at various enzyme concentrations (0.01-0.2 %), incubation temperature (30-55 oC), and incubation time (30-100 min.) of treatment. A second-order Central composite (CCD) was employed to identify the effect of independent variables on the final product.  Results: In this study, a statistically significant difference (P<0.05) was observed within the process variables on nutritional profiles of casimiroa fruit juice. Furthermore, the enzyme treatment reduced the cloudy appearance of casimiroa fruit juice and improved its clarity of juice. The coefficient of determination and R2 values for the dependent variables were almost greater than 0.8. This study revealed that clarity, viscosity, TSS, TA, pH, phenolic compounds, flavonoids, β-carotene, ascorbic acid, Na, K, Ca, Fe, Zn, P, and overall acceptability were significantly (p<0.05) correlated to incubation temperature, incubation time and enzyme concentration. Incubation time and enzyme concentration were the most important factors affecting the characteristics of the casimiroa fruit juice as they exerted a highly significant influence (p<0.05) on the dependent variables.  Conclusion: In conclusion, enzyme treatment improves qualities of fruit juice and the overall optimization suggests that enzymatic-treated juice made with 75% fruit pure, 21.25% water, 2.63 % sugar, and 1.13 % citric acid with process variables of incubation temperature (44.01 0C), incubation time (62.74 min.) and enzyme concentration (0.2 %), respectively achieved the best formulation for this combination of variables with a desirable of 0.9029.